Restoring lumbar spine stiffness using an interspinous implant in an ovine model of instability. (March 2016) - Szpalski, Marek; Gunzburg, Robert; Colloca, Christopher J.; Kosmopoulos, Victor; Hegazy, Mostafa Afifi; Freeman, Brian J.C.; Fabeck, Laurent
Abstract: Background : The objective of this study was to determine the effect of an interspinous implant on lumbar spine stability and stiffness during dorsoventral loading. Methods : Twelve Merino lambs were mechanically tested in vivo. Oscillatory (2 Hz) loads were applied to L2 under load control while displacements were monitored. Tri-axial accelerometers further quantified adjacent L3–L4 accelerations. Dorsoventral lumbar spine stiffness and L3 and L4 dorsoventral and axial displacements were determined over six trials of 20 cycles of loading. Four conditions were examined: 1) initial intact, 2) following destabilization at L3–L4, 3) following the insertion of an InSwing ® interspinous device at L3–L4, and 4) with the implant secured with a tension band. Comparisons were performed using a one-way ANOVA with repeated measures and post-hoc Bonferroni correction. Findings : Compared to the intact condition, destabilization significantly decreased lumbar stiffness by 4.5% ( P = .001) which was only recovered by the interspinous device with tension band. The interspinous device caused a significant 9.75% ( P = .001) increase in dorsoventral stiffness from destabilization that increased 14% with the tension band added ( P = .001). The tension band was responsible for decreased displacements from the intact ( P = .038), instability ( P = .001), and interspinous device ( P = .005) conditions. Dorsoventral L3–L4 motion significantly improved with the interspinous device ( P = .01) and the addition of the tension band ( P = .001). No significant differences in L3–L4 intersegmental stability were noted for axial motion in the sagittal plane. Interpretation : This ovine model provided objective in vivo biomechanical evidence of lumbar instability and its restoration by means of an interspinous implant during dorsoventral spinal loading. Highlights: We model lumbar instability in the sheep spine in vivo. We tested the effect of an interspinous implant on spinal stiffness recovery. The interspinous implant secured by a band provided the most spine stability. Adjacent segment biomechanics were also influenced by the interspinous implant.